Keabsahan Pengusulan Pejabat Kepala Pemerintahan Negeri Haya - Zain Arifin Hatuluayo Selano; Sherlock Halmes Lekipiouw; Miracle Soplanit (PATTIMURA Law Study Review, 2023)
Regional Government defines regional autonomy as the authority and obligation of an autonomous region to regulate and manage government affairs and the interests of local communities in accordance with statutory regulations. Saniri Negeri is a vehicle for democracy that is formed based on the customs that apply in that traditional country. The purpose of this research is to examine and discuss whether the regent's actions in appointing the head of the Haya state government were based on applicable laws. The research method used is normative juridical, namely research on rules, norms and legal principles based on statutory regulations. The problem approach used is a normative legal approach, namely the conceptual approach, case approach and statutory approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Techniques for collecting legal materials through literature study. Next, it was analyzed qualitatively. The results of the research concluded that the regent's action in using his authority to appoint an official outside the proposed saniri of the country/village of Haya without involving the saniri of the country in the vacancy at the end of the term of office of the king of one of the parents' houses of Haya village was not based on the applicable laws and regulations. Responsibility for regulations carried out by the regent in carrying out his authority is considered flawed and categorized as exceeding the limits of his authority.